Assessment of water quality using the Canadian index CWQI - Case study of the Orontes River in Hama Governorate – Syria - AlFattamah, Ammar Mahmoud; Sabbouh, Houssam Shafeek; Jafar, Raed Salman (Journal of engineering sciences and information technology, 2022)
The aim of the study is to address the issues and associated health risks due to consumption of high pollution parameters in parts of the Orontes River basin, Hama governorate, Syria using the Canadian Water Quality index (CWQI), as an appropriate tool in classifying and studying the impact of spatial and seasonal changes on pollution loads. In this study, 9 parameters (pH, BOD5, NH4+, CL-, PO4-, Na+, Total Hardness, Turbidity, Conductivity) were taken from 9 stations along the river, One-Way ANOVA and Pearson correlation coefficient were applied separately for all parameters, and a value of ρ<0.05 were observed when Appling One-Way ANOVA test on all parameters and for spatial and seasonal changes. The CWQI formula was used to calculate a final index value for different spatial and seasonal changes. Water quality in 8 Locations (Al-Rastan Dam Exit, Ghor Al-Asi, Al-Ghashalah Bridge, Al-Rabaa Nowair Bridge, Al-Daheriya Bridge, Arzah Bridge, Khattab Bridge, Mahradeh Dam Lake) ranges between (33-36) and classified as poor according to the Canadian Water Quality Index, in Whereas, the value of water quality index in location (Jisr Al-Jinan) was (57), and classified as marginal. Regarding the seasonal changes: CWQI water quality index values ​​ranged between (33-34) and classified as poor in all seasons of the year (spring, summer, autumn, winter) and therefore the water of the Orontes River in Hama Governorate was poor for drinking water, according to all classifications used in this research.